AGING PROCESS AND SOCIAL SECURITY SYSTEM IN INDIA - Dr. Pallavi Sinha Das (Galaxy International Interdisciplinary Research Journal, 2021)
Nearly 80% of elderly population works in India, increasing age does not give them any relief from physical work. Moreover, this is because of lack of social and financial security, elderly population in India has to work to meet their necessities as long as physically possible. The present scenario shows that there is continuous rise in the elderly population in last decade and it is projected to rise further in coming years. On the other hand, because of the demographic rise in the population of the elderly people, the focus drives for the more emphasis on the socio-economic implications it holds for society, and providing them better quality of life.The needs and problems of the elderly vary significantly according to their age, socio-economic status, health, living status and other environmental features. The paper proposes that there is a need to look at the elderly in positive way with respect to their productive nature to the family rather than simply associating elderly to dependency, it will also look into social security scenario, globally and in India. Last but not the least suggestions for improvement of social infrastructure and looking after elderly as resource for country.